Surgical management of adnexal masses in adolescent females at a tertiary centre in India: a case series - Thakur, Meenakshi; Rana, Deepti; Verma, Meenakshi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
This case series details 15 adolescent females (aged 13–19 years) who underwent surgery for adnexal masses from January 2022 to January 2025. The most common presenting complaint was abdominal pain (80%). Imaging with ultrasound and MRI showed large complex cystic masses (>10 cm) in 66.7% of patients. Laparotomy was performed in 12 patients (80%) due to large size and limited resources, while laparoscopy was feasible in 3 cases (20%). Histopathology revealed benign lesions in all cases: mature cystic teratoma (66.7%), serous cystadenoma (20%), and functional cyst (13.3%). Mild elevations in CA-125 and LDH were noted in some patients, but no malignancy was identified. Ovarian preservation was achieved in 60% of cases. All patients recovered uneventfully, with no complications or recurrences at six-month follow-up. These findings support the benign nature of adolescent adnexal masses and emphasize individualized surgical management with fertility preservation.